Morphological Ensembles of N-Doped Porous Carbon Derived from ZIF-8/Fe-Graphene Nanocomposites: Processing and Electrocatalytic Studies - Thomas, M.; Illathvalappil, R.; Kurungot, S.; Nair, Balagopal; Mohamed, A.; Anilkumar, G.; Yamaguchi, T.; Hareesh, U. (Wiley - V C H Verlag GmbH & Co. KGaA, 2018)
© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim Engineering the active site density of porous carbon catalysts for enhanced electrocatalytic activity is the current focus in the quest for economically viable fuel cells. Herein, we synthesise ZIF-8/Fe-graphene composites for the formation of N and Fe co-doped carbon with diverse morphologies ranging from tubes and sheets to frameworks of carbon. A synthetic strategy involving the one pot synthesis of ZIF-8 based composites is accomplished by the reaction of 2-methylimidazole with mixed Zn/Fe salt solution containing graphene dispersions. The high temperature heat treatment of this precursor mix yielded micro-meso porous architectures of N, Fe co-doped carbon with dispersions of Fe/Fe3C. An onset potential value of 0.95 V and a half-wave potential of 0.82 V coupled with excellent durability and stability in alkaline medium indicated improved electrocatalytic performances over its commercial Pt/C counterpart. The appreciable electrocatalytic properties of the synthesized carbon are attributed to its morphological diversity, hybrid structure, high N doping and its heteroporous characteristics. The dispersed Fe/Fe3C and FeNx sites facilitated enhanced oxygen adsorption and the graphene inclusions in the composite provided retention of high nitrogen contents.